It Looks Like “Theirs”: When and Why Human Presence in the Photo Lowers Viewers’ Liking and Preference for an Experience Venue - Lu, Zoe Y; Jung, Suyeon; Peck, Joann (Journal of Consumer Research, 2024)
Abstract Consumers and marketers often post photos of experiential consumption online. While prior research has studied how human presence in social media images impacts viewers’ responses, the findings are mixed. The present research advances the current understanding by incorporating viewers’ need for self-identity into their response model. Six studies, including an analysis of field data (14,725 Instagram photos by a top travel influencer) and five controlled experiments, find that the presence (vs. absence) of another human in the photo of an identity-relevant experience (e.g., a vacation, a wedding) can lower viewers' liking and preference for the venue (i.e., the vacation destination, the wedding venue) in the photo. This effect is mediated by viewers' feelings of others' ownership of the venue and moderated by the relevance of the experience to the viewer’s self-identity as well as the distinctiveness of the human in the photo. This research is the first to investigate the impact of human presence in shared photos through the lens of psychological ownership and the identity-signaling function of ownership. The findings offer practical insights into when marketers should avoid human presence in advertisements and how to mitigate the negative impact of human presence in online photos.